Correlation analysis between epicardial adipose tissue and acute coronary syndrome - Gao Zhihong; Zuo Yuqiang; Jia Linyi; Yin Yuling; Yang Xu; Xu Lei; Hao Zengfang (Scientific Reports)
Abstract To investigate the correlation between the density and volume of epicardial adipose tissue(EAT)and acute coronary syndrome (ACS). This study included 355 subjects (mean age: 60.65 ± 9.67 years; 54.65% male), comprising 175 patients with ACS and 180 without ACS. Propensity score matching was applied to balance the variables between the two groups, resulting in 96 successfully matched pairs. Clinical data, epicardial adipose tissue volume (EATV), and epicardial adipose tissue density (EATD) were compared. Independent factors influencing ACS were identified using logistic regression analysis, and the predictive ability of each variable was evaluated using receiver operating characteristic (ROC) curves. Systolic blood pressure, EATV, EATD, fasting blood glucose, triglycerides, and high-sensitivity C-reactive protein were significantly elevated in the ACS group compared with the non-ACS group (all p < 0.05). Spearman correlation analysis revealed a moderate positive correlation between EATV and BMI (r = 0.444, p < 0.001), while EATD showed a weak negative correlation with age (r = -0.177, p = 0.014) and a weak positive correlation with EATV (r = 0.239, p = 0.001). Univariable regression analysis demonstrated that both EATV (OR: 2.018, 95% CI: 1.334–3.052) and EATD (OR: 5.341, 95% CI: 3.293–8.663) were associated with ACS. After adjusting for other risk factors, logistic regression model confirmed that EATV (adjusted OR: 1.892, 95%CI: 1.211–2.955) and EATD (adjusted OR: 6.942, 95%CI: 3.875–12.437) were independent predictors of ACS (both p < 0.001), with EATD showing the highest predictive value (AUC = 0.859). This study identifies a close relationship between EAT and ACS, highlighting EATD and EATV as independent influencing factors for ACS. Among them, EATD demonstrated a stronger predictive value for ACS than both traditional risk factors and EATV.